The extracellular role of DJ-1 in the regulation of signaling pathways: implications for Parkinson’s disease - Neves, Margarida Seco Martins Marques (2021)
Parkinson’s disease (PD) is a progressive neurodegenerative disorder with no cure, characterized by the loss of dopaminergic neurons in the brain's substantia nigra pars compacta. Despite extensive research, the exac t causes and mechanisms leading to the development of PD are still unknown. Among the hereditary forms of PD, mutations in the DJ - 1 gene have been associated with an autosomal recessive early -onset disease type. The DJ -1 protein plays an important role in the defensive response to oxidative stress, in which the modulation of signaling pathways is pointed out as a central mechanism. While such cytoprotective function has been most described at the intracellular level, increasing evidence also confirm s the ability of the protein to mediate a protective effect from the extracellular space upon its secretion. However, the precise mode of action of the extracellular DJ -1 or the pathological implications of its mutations is still misunderstood. In this sense, the aim of this work was to elucidate the mechanisms of action of extracellular DJ -1 with particular consideration to its role in signaling pathways modulation. To accomplish this, an interatomic study was performed to identify the network of interactions esta blished by DJ - 1 in the extracellular space, followed by a phospho -motif profiling analysis to assess the pathological impact of DJ -1 mutants in kinase - related signaling. From the interactomic analysis of the secretome of SH -S5Y5 cells after the addition o f exogenous DJ - 1 in the presence or absence of oxidative stress , it was possible to identify a set of 28 potential extracellular DJ - 1 -interactors possibly involved in the neuroprotective action exerted by DJ - 1. Additionally, the modulation of such interactions was also assessed in oxidative stress conditions. The list of potential interactors identified in this work confirms an important involvement of DJ -1 in the modulation of signaling pathways from the extracellular environment. TSP1, THBR, MIF , and CAD1 1 , some of the binding partners of DJ - 1 identified in this work, are known to be involved in the regulation of some signaling pathways such as PI3K/Akt, TGF -β, ERK1/2, Wnt , and PLD - related signaling. In turn, from the “semi -targeted” phospho -motif profiling assay aimed to assess the differential modulated signaling events by the exogenous addition of DJ - 1 native and missense mutants M26I and E163K, it was possible to confirm that both mutations elicited alterations in the kinase - mediated substrate phosphorylation profile in comparison to the condition of WT -DJ -1 extracellular stimulated SH -S5Y5 cells. In fact, a generally decreased kinase activity was observed, with the E163K -DJ -1 isoform exhibiting a more prominent impact associated with a significant reduction i n the activity of Akt, ATM/ATR, AMPK, CK2, CDKs , and PKC. Nevertheless, the results also denote that both mutants of DJ -1 had a similar pattern of alteration in the phosphorylation of some of the substrates analyzed , which could be an indication of convergent pathological mechanisms. In conclusion, this work contributed with important knowledge into the biological role of extracellular DJ -1 in the modulation of signaling pathways and elucidated the impact of mutations in the activity of the protein. Following studies should be conducted to validate the obtained results and support the hypotheses raised in this work. Ultimately, the presen t findings also reflect valuable insights into the understanding of the molecular mechanisms implicated in PD.